1991
DOI: 10.17161/fec.v24i4.7537
|View full text |Cite
|
Sign up to set email alerts
|

Social Coordination as a Component of Social Competence in Young Children with Disabilities

Abstract: Substantial evidence shows that young children with disabilities frequently have difficulty with social interaction (Guralnick & Weinhouse, 1984). Although the interactions of children with disabilities and their peers do not seem to be any more negative than the interactions of nondisabled children and their peers, evidence suggests that the overall frequency of interactions is much lower (Beckman, 1983;Guralnick, 1990;Guralnick & Weinhouse, 1984). For example, Beckman (1983) found that preschool children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Kim et al (2003) found that children with disabilities engaged in more solitary play behaviors and nonplay behaviors than peers who were typically developing. In addition, children with developmental disabilities tended to engage in more symbolic, complex play when they were alone rather than when peers were present (Lieber & Beckman, 1991), indicating that when social interactions with peers are possible, children with developmental disabilities like ASD may not participate in socially oriented play behaviors, thus missing opportunities to engage in social interactions.…”
Section: Social Engagement Of Preschool Children With Asdmentioning
confidence: 99%
“…Kim et al (2003) found that children with disabilities engaged in more solitary play behaviors and nonplay behaviors than peers who were typically developing. In addition, children with developmental disabilities tended to engage in more symbolic, complex play when they were alone rather than when peers were present (Lieber & Beckman, 1991), indicating that when social interactions with peers are possible, children with developmental disabilities like ASD may not participate in socially oriented play behaviors, thus missing opportunities to engage in social interactions.…”
Section: Social Engagement Of Preschool Children With Asdmentioning
confidence: 99%
“…The SocBS. The selection of the specific behaviors used to create this scale was informed by cognitivedevelopmental theory and related descriptive studies of children's social behaviors (Bailey et al, 1993;Lieber & Beckman, 1991b;Odom & Ogawa, 1992;Parten, 1932). We began with an analysis of Parten's Scale of Social Participation (1932), which is widely used in contemporary research to examine social or social communicative behavior in a play context (Bailey et al, 1993;Craig-Unkefer & Kaiser, 2003;Farver, Kim, & Lee, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Although we were able to adopt Parten's less complex social measures (e.g., Solitary, Onlooking) for this study, we needed to replace her more complex measures (e.g., Associative, Cooperative) to disentangle the quality of social interaction from the quality of play activity. We determined that the social behaviors that were more complex than Onlooking could be distinguished based on the presence or absence of social coordination (Lieber & Beckman, 1991b). We therefore added the new categories of Uncoordinated Social and Coordinated Social to Parten's categories of Onlooking and Solitary activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations